In vitro evaluation of the antibacterial behavior of a self-etch adhesive associated with chlorhexidine - Roberta Bento RODRIGUES; Nereida Mello GIOPPO; Priscilla do Monte Ribeiro BUSATO; Marcio José MENDONÇA; Veridiana CAMILOTTI (Universidade Estadual Paulista, 2019)
Abstract Introduction Adhesive technology has been developed quickly since its introduction about fifty years ago. Its goal is to produce a close contact within enamel and dentin. Failures in this process could result in microleakage, and allow the infiltration of bacteria, fluids and ions. Recent studies have been shown the use of chlorhexidine associated with adhesive systems can be able to inhibit the bacteria action. Objective The aim of this study was to evaluate the addiction of different percentages of chlorhexidine to a self-etch adhesive. Methodology The solution of digluconatechlorhexidine was increased to the primer of the two pass self etch adhesive to create a 0.5%, 1.0% and 2.0% chlorhexidine primer solution and after they were distributed in four groups (G1, G2, G3 and G4). Saliva samples (N=10) were used to test bacteria activity. Result They were spread in a blood medium with filter paper disks containing the different treatments. After the incubation, the inhibitions halos formation were evaluated. Conclusion This study demonstrated that, in vitro, the addition of different percentages of chlorhexidine digluconate to the self-etch adhesive induced inhibited halos at bacteria of saliva samples, independent from their concentration.